PENGELOLAAN SARANA CHROMEBOOK UNTUK MENINGKATKAN KINERJA PELAKSANAAN ASESMEN NASIONAL DI SEKOLAH (STUDI KASUS DI SMPN 3 KECAMATAN AIR BESAR KABUPATEN LANDAK) - Defirman Defirman; Aunurrahman Aunurrahman; M. Syukri (Universitas Tanjungpura, 2022)
Good performance is a determining means in achieving goals that can be achieved by a person or group. In order to achieve the educational goals in 2021, the government is implementing a computer-based national assessment program. As a support, management of school facilities is required. management facilities are very important, because the process carried out by schools to utilize them so that the implementation of the national assessment can run as it should. Form of qualitative research with approach a case study. Principal research subjects, teachers and students. Methods of data collection by documentation, observation and,interview. Main findings: (1) Planning for chromebook facilities begins with the establishment of a committee contained in the decision letter (2) setting up chromebook facilities, the inventory process is carried out by checking based on the Minutes of Goods Handover. Storage of chromebooks is limited to a safe cupboard protected from moisture. The chromebook maintenance facility is preventive in nature when the national assessment is carried out by resting the chromebook for a while before being used again for testing. (3) The use of chromebook facilities is the responsibility of the school principal and appoints teachers who serve as proctors and technicians. In carrying out the assessment the national students were guided by the teacher so that the implementation of the assessment ran smoothly (4) The removal of the chromebook facility could not be carried out, this was because there had been no findings of damage or problems with the chromebook facility. (5) The National Assessment is attended by grade 8 students, using the dare mode chromebook facility, taking into account the operational costs of carrying out the national assessment. The conclusion of the chromebook management facility to improve the performance of the implementation of the national assessment, is in accordance with the principles of facility management.